Recombinant production platform for Group A Streptococcus glycoconjugate vaccines - Sowmya Ajay Castro; Ian J. Passmore; Didier Ndeh; Helen Alexandra Shaw; Alessandro Ruda; Keira Burns; Sarah Thomson; Rupa Nagar; Kathirvel Alagesan; Mark Reglinski; Kieron Lucas; Sherif Abouelhadid; et al. (npj Vaccines)
Abstract Group A Streptococcus (Strep A) is a human-exclusive bacterial pathogen killing annually more than 500,000 patients, and no current licensed vaccine exists. Strep A bacteria are highly diverse, but all produce an essential, abundant, and conserved surface carbohydrate, the Group A Carbohydrate, which contains a rhamnose polysaccharide (RhaPS) backbone. RhaPS is a validated universal vaccine candidate in a glycoconjugate prepared by chemical conjugation of the native carbohydrate to a carrier protein. We engineered the Group A Carbohydrate biosynthesis pathway to enable recombinant production using the industry standard route to couple RhaPS to selected carrier proteins within Escherichia coli cells. The structural integrity of the produced recombinant glycoconjugate vaccines was confirmed by Nuclear Magnetic Resonance (NMR) spectroscopy and mass spectrometry. Purified RhaPS glycoconjugates elicited carbohydrate-specific antibodies in mice and rabbits and bound to the surface of multiple Strep A strains of diverse M-types, confirming the recombinantly produced RhaPS glycoconjugates as valuable vaccine candidates.